Inventarisasi dan Kajian Objek Pemajuan Kebudayaan dan Cagar Budaya Di Kabupaten Pacitan - Agoes Hendriyanto; Bakti Sutopo; Sri Iriyanti; Muhammad Rafid Musyaffa (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to inventory and assess Cultural Advancement Objects (Objek Pemajuan Kebudayaan/OPK) and cultural heritage in Pacitan Regency within the framework of the Indonesiana 2025 Program. This research employed a descriptive qualitative approach conducted across 12 sub-districts in Pacitan Regency, East Java Province. Data were collected through field observations, in-depth interviews with cultural practitioners, community leaders, traditional custodians, and local historians, documentation, and historical studies. The collected data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that Pacitan Regency possesses abundant cultural resources, encompassing prehistoric archaeological sites, early socio-political systems, ritual traditions, performing arts, oral traditions, traditional knowledge, and colonial heritage that continue to exist today. These findings demonstrate the continuity of civilization and cultural acculturation that shape the cultural identity of the Pacitan community. This study provides a comprehensive scientific inventory that can serve as a reference for cultural preservation policies and supports sustainable cultural advancement in accordance with Law Number 5 of 2017 concerning Cultural Advancement.